Monitoring and Assessment of Water Quality in Coastal Lake using High Resolution Imagery and GIS - Ali, Tarig (2017)
Dubai has been an example of rapid development in recent years, adversely affecting water quality in the surrounding areas. One such effect is the reoccurring algal bloom (high chlorophyll-a concentration) in Dubai Creek, a coastal lake in Dubai. The objectives of this study were to retrieve chlorophyll-a from Dubai Sat-1 imagery and to further investigate its relationship to different nutrients in the creek. Spectral models of chlorophyll-a were developed from two DubaiSat-1 images acquired in 2010 and 2011. The models showed high correlation (R-squared values of 87.7%and 89.1%, respectively) with field water quality data collected at the monitoring stations operated by Dubai Municipality. Exploratory Regression (ER) analysis was then performed in GIS to study the relationship between spectral-based chlorophyll-a and nutrients. Although the ER nalysis showed low overall correlation, relatively high R-squared values were obtained at the Sewage Treatment Plant outfall location.